ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI PEMBIAYAAN MURABAHAH PADA BANK SYARIAH MANDIRI PERIODE 2008.01-2011.12 - Mustika Rimadhani; Osni Erza (Media Ekonomi, 2011)
Murabaha financing is the most dominant in Indonesia Islamic banking compared to other financial products, it also dominates the Islamic banks in other countries. This method is becoming very popular because it is the nature of murabaha financing has required rate of profit that is definitely in accordance with the terms agreed upon. This study aims to determine the variables that influence the murabaha financing at Bank Syariah Mandiri, which consists of Third Party Funds (TPF), Profit Margin, Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR). The data used in this study is a secondary data with monthly period 2008:012011:12. The analysis technique used is the Multiple Linear Regression by OLS (Ordinary Least Square). Based on the research results that the Third Party Funds (TPF) has positive and significant, Margin keutungan negative and insignificant, NPF has positive and significant effect, FDR has negative and insignificant.Keywords :Murabaha Financing, Third Party Funds (TPF), Profit Margin, NonPerforming Financing (NPF), Financing to Deposit Ratio (FDR)